Research on Circulating Current Suppression Control of Parallel Inverters - Yibiao Fan; Lixia Tong; Xiaoping Wang; Xiaowei Cai; Zhihe Fu; Junhui Zhou; Shuangmao Huang; Xingkui Mao (Energies)
Circulating current suppression can effectively improve the reliability and redundancy of parallel inverter systems. The mechanism and influencing factors of the low- and high-frequency zero-sequence circulating current (ZSCC) are analyzed in this study. Based on a mechanism analysis and the built mathematical model, the composite control strategy of zero-sequence voltage difference (ZSVD) compensation and virtual inductance is proposed to suppress the low- and high-frequency ZSCC. In the composite control strategy, the low-frequency ZCSS (LF-ZCSS) is suppressed by the ZSVD compensation method, and the HF-ZCSS is suppressed by the virtual inductance method. The ZSVD compensation is incorporated into the SVPWM as an input to regulate the modulation and suppress the LF-ZCSS, and virtual inductance is introduced into the current control loop to suppress the HF-ZCSS. A parallel system prototype composed of two 6 kW inverters is constructed. The experiments show that the ZSCC of the parallel system is reduced by 45%, which verifies the effectiveness of the proposed composite control strategy.